Meru Architecture in Bali : History, Function and Challenges - Wardana, Made Rai (Bali Tourism Journal, 2024)
Meru is a sacred structure in Balinese architecture, symbolizing Mount Sumeru in Hindu-Buddhist cosmology. Introduced by Mpu Kuturan in the 11th century, Meru is a key feature of Balinese temples, representing the connection between the divine and earthly realms. The tiered roof, which can range from one to eleven layers, reflects different levels of the universe, with higher tiers holding greater spiritual significance. Meru is not only a site of worship for deities and ancestors but also plays a crucial role in traditional ceremonies, such as the ngaben cremation rites. One of the remarkable aspects of Meru is its earthquake-resistant design. Built with natural materials like ijuk (sugar palm fibre) and ironwood, its proportional structure and construction techniques allow it to withstand seismic shocks effectively. However, while Meru can endure earthquakes, it remains vulnerable to fire, especially due to lightning strikes. The dry, flammable ijuk used for the roof makes Meru susceptible, as evidenced by recent fires at temples like Ratu Gede Bima Sakti and Dadia Bingin. Efforts to protect Meru from fire hazards are underway, including raising community awareness and improving fire safety protocols. Despite these challenges, Meru continues to stand as a powerful symbol of Bali’s spiritual and cultural identity, blending ancient traditions with modern efforts to preserve this sacred architecture.